Integrated management of hydroponic wastewater for complete water recycle and cyanobacteria cultivation using an electric conductivity-based tool. (September 2022) - Samiotis, Georgios; Lykas, Christos; Ristanis, Ilias; Stimoniaris, Adamos Z.; Amanatidou, Elisavet
Abstract: This work presents an integrated management process for hydroponic wastewater (HWW) reuse, by developing an electric conductivity-based tool that calculates recycled nutrient solutions' enrichment requirements and indicates their proper treatment. Treatment includes advanced methods and Synechococcus elongatus PCC 7942 (S7942) cyanobacteria cultivation for the removal/recovery and utilization of nutrients contained in HWW. The results showed that HWW can be utilized as substrate for S7942 cultivation. Increasing initial substrate nitrate‑nitrogen concentration from 389 ± 3 mg L −1 to 2132 ± 17 mg L −1 increases nitrogen assimilation from 0.131 mgNO3 -N mgVSS −1 to 0.163 mgNO3 -N mgVSS −1 . Similarly, increasing initial substrate phosphate-phosphorous concentration from 8.4 ± 0.2 mg L −1 to 138.2 ± 5.0 mg L −1 increases phosphorous assimilation from 0.022 mgPO4 mgVSS −1 to 0.133 mgPO4 mgVSS −1 . The advanced ion exchange treatment had efficiency >98 %. Adsorption with activated carbon and nanomaterials showed selective removal of nitrates, phosphates, calcium and magnesium. Sonication further increased nanomaterials' selectivity. Graphical abstract: Unlabelled Image Highlights: Process control via electric conductivity and once determined ion profile Hydroponic effluents valorization via cyanobacteria cultivation Nitrogen assimilation increased to 0.163 mgNO3 -N mgVSS −1 at 2132 mgNO3 − L −1 nitrates. Phosphorous assimilation increased to 0.133 mgPO4 mgVSS −1 at 138.2 mgPO4 −3 -P L −1 . Sonication enhanced nanomaterials' Carbon black and Cloisite 30B ion selectivity.